Assessment of Work-Life-Balance of Nursesbased on Demographic profile - et al., Mr.R. Manivannan (International Journal of Advanced Science and Technology, 2019)
The aim ofthe study is to find out the relationship between demographic profile and work-life-balance among the nursing professional. Nurses are playing importance role in the hospital performance and family well being. This study is applied descriptive research procedure to accomplish the purpose of the objective. The variables of the study are work life balance and demographic profile by experienced nurses. The target population is defined as nurses who had completed five years of experience and who are all working in Cuddalore District, Tamilnadu, India. In this district, 4040 nurses are working in public and private hospital. From in this population, ten percent of subjects 404 are approached to participates this study. The degree of work life balance has been measured with 15 statements. Participants are asked to rate themselves in the seven point scale. Where seven stands for strongly agree one stands for strongly disagree. Descriptive statistics chi square analyses have been applied. It is found that nurses are able to balance their work and family effectively. They also felt thatthe age group, educational qualification and family status are having relationship with Work life balance for the nursing profession.